1998
DOI: 10.2337/diabetes.47.3.352
|View full text |Cite
|
Sign up to set email alerts
|

Palmitate and myristate selectively mimic the effect of glucose in augmenting insulin release in the absence of extracellular Ca2+.

Abstract: Under Ca2+-free conditions, activation of the pancreatic beta-cell with forskolin and 12-O-tetradecanoylphorbol 13-acetate (TPA) is permissive for the augmentation of insulin release by glucose and other nutrients. The ability of fatty acids to mimic the effect of glucose and thereby augment insulin secretion in the absence of extracellular Ca2+ is the focus of the present study. In the absence of extracellular Ca2+, glucose, palmitate, and myristate had no effect on insulin release. When, under Ca2+-free cond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
30
2

Year Published

1999
1999
2008
2008

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 26 publications
0
30
2
Order By: Relevance
“…The same final concentrations of DMSO were present in paired control tubes. At the end of test incubations, the medium was aspirated and kept at -20°C until radioimmunoassayed for insulin, where rat insulin was used as the standard (3,5,15,16). Glucose oxidation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The same final concentrations of DMSO were present in paired control tubes. At the end of test incubations, the medium was aspirated and kept at -20°C until radioimmunoassayed for insulin, where rat insulin was used as the standard (3,5,15,16). Glucose oxidation.…”
Section: Methodsmentioning
confidence: 99%
“…Recent direct supportive evidence includes the effect of fatty acids to augment insulin secretion (13,14). Furthermore, it has been suggested that malonylCoA and LC-CoA could be responsible for the K ATP channel-independent pathways of glucose signaling (15,16). Following up on this hypothesis, we examined the effects of cerulenin, a fungal antibiotic that inhibits protein acylation H. YAJIMA AND ASSOCIATES (17,18), on insulin release.…”
mentioning
confidence: 99%
“…In fact, phorbol ester dependent PKC stimulation inhibits intracellular insulin signalling in vitro 29 and in pancreatic islet cell PMA stimulates insulin release and hyperinsulinaemia. 30 In summary, the present study shows that part of the abnormal kinetics of H ϩ i activation of RBC NHE in hypertensives are secondary to altered PKC regulation. In normotensives, the sigmoidal activation of Na ϩ influx through the NHE indicates that the transporter can be rapidly activated by changes of cell pH: on one hand, a fall of cell pH briskly stimulates Na ϩ influx and H ϩ efflux through the transporter; on the other hand an increase of cell pH inhibits the transporter and prevents further alkalinization.…”
Section: Discussionmentioning
confidence: 55%
“…This is an ATPsensitive K + channel-independent insulinotropic action [8]. Interestingly, NEFA also augments GSIS via a mechanism that does not involve this channel [5].…”
mentioning
confidence: 98%
“…This study is of great interest to us because we consider the malonyl-CoA pathway and the resultant NEFA augmentation of insulin exocytosis to be vital for glucose-stimulated insulin secretion (GSIS), especially for the replenishment of the readily releasable pool of insulin granules during secondphase secretion [2,3]. Prior to the visual demonstration and molecular elucidation of intracellular granule trafficking, this process was known conceptually as 'potentiation' [4], 'augmentation' [5] or 'amplification' [6].…”
mentioning
confidence: 99%